Basic forms (genres) of literature and the relationship between poetry and drama - Mahmood, Fazil Majid; Ali, Aram Omer (JOURNAL OF LANGUAGE STUDIES, 2023)
The research entitled (Basic Forms of Literature and the Relationship between Poetry and Drama) is an attempt to present accurate information about the genres of literature and point out the differences and relationships between them. In order to find the relationship between poetry and drama, which is the main purpose of our research, the beginnings of distinguishing literary genres go back to Aristotle's book on the art of poetry. That is, the classification that existed from the beginning until the Middle Ages dates back to the time of Aristotle, but what exists today, although there are differences between them, there are many commonalities and similarities between the elements and genders. Through its results, the research describes the relationship between drama and poetry as a historical century and from there goes to find the closest points of the relationship between poetry and drama.